Identifikasi Ikan Genus Mystus Dengan Pendekatan Genetik - Taufik Budhi Pramono; Diana Arfiati Arfiati; Maheno Sri Widodo; Uun Yanuhar Yanuhar (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2017)
The fish of the Bagridae Family in Indonesia reach until 60 species and one of them is from the genus Msytus. The method is used for fast and accurate species identification was needed. DNA barcoding was a new identification method with molecularly approach. The CO1 gene was amplified and PCR products were sequenced and analyzed using bioinformatics software. Editing of sequencing results and determining the nucleotide composition were analyzed with Mega5 software. The DNA sequence was aligned with ClustalW vers. 1.4. Sequences are compared with GenBank data using BLAST (Basic Local Aligment Search Tools) and BOLDSystems. Phylogenetic tree was made using Neighbor_Joining method. One example of the identification of fish from the confirmed Mystus genus is Mystus nigriceps being the Mystus singaringan.